A study on complexity measures - Andri Pradana (2013)
In this study, we develop a technique to measure randomness and complexity for various systems. The measures were applied to different systems: the pseudo-random number generators (C-native rand() & lrand48(), and the Mersenne twister algorithm), the arc-fractal system, and the Abelian Manna sandpile model (AMM). The aim was to reveal, to some extent, the internal structure of these systems.